Differences of perception of responsible purchase intention according to demographic characteristics of Turkish consumer - KOÇOĞLU SAZKAYA, MERVE (My University, 2023)
Today, problems of increasing rapid consumption, global warming, thirst and hunger threaten the whole world. This situation has taken its place primarily on the agenda not only of states but also of businesses that cause this problem. In academic studies, studies on these negative situations are handled within the framework of the concept of sustainability. Therefore, almost all humanity becomes conscious by confronting this negative situation. These negative situations are changing people\"s lifestyles and preferences. Responsible purchasing behavior that affects the whole world is an example of this. Responsible purchasing behavior is purchasing environmentally friendly products that are produced using recycled materials in the production process. All over the world, some of the consumers have started to decide by considering the production process of the products they want to buy. Consumers look at whether businesses exhibit environmentally friendly behavior in the production process and whether they use recycled materials. Realizing this situation, manufacturers are producing products made from recycled materials while diversifying their products. In other words, many businesses offer their customers a choice of products made from recycled materials. While responsible purchasing behavior is increasing rapidly in the world, it is almost at the beginning stage in Turkey. Therefore, there is a need to learn about the responsible purchasing behavior of Turkish consumers. In this context, in this study, it is aimed to determine whether there are significant differences in the responsible purchasing intentions of Turkish consumers according to demographic variables such as gender, age, income level, marital status, education level, place of residence. The fact that there are not many academic studies on determining the responsible purchasing behavior of Turkish consumers in the literature review reveals the originality of this research. At the same time, the results of the research will provide information that will help manufacturers producing from recycled materials to develop effective strategies to persuade consumers to buy these products and to increase responsible purchasing behavior in Turkey.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)